Nanoherbal Ocimum Basilicium L Reduce Mda And Increase Sod Level In Wistar Rats Induced Stz - Hanjaya Hanjaya; Sahna Ferdinand; Bungaran Sihombing; Djohan Djohan (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2022)
One of the public health problems that is very serious and requires proper treatment for sufferers is diabetes mellitus (DM). An increase in plasma glucose levels that exceeds normal limits is one of the basics for diagnosing diabetes. This study aim to determine the antidiabetic activity of Nanoherbal Extract of Ocimum Basilicum L. This is an experimental study in which the research group was divided into seven groups, each including five rats weighing 200-250 grams. Which are (normal group, negative group, metformin, nanoherbal 25, 50, 100, and 200 mg/kgBW). Rats were induced by STZ 75 mg/kgBW + NCT 120 mg/kgBW until the blood glucose is above 200 mg/dL. The highest level of SOD is the control group 63.984 ± 2,065 ng/mL and the lowest is negative group is 22,41 ± 2,06 ng/mL. For group that given treatment show that the highest SOD level is in dose 200 mg/kgBW 71,72 ± 0,90 ng/mL and the lowest is in dose 25 mg/kgBW 31,814 ± 1,11 ng/mL and the group given metformin is 68,52 ± 32,39 ng/mL. The highest level of MDA is in group control which given only STZ and NCT 37,522 ± 1,64 ng/mL and the lowest MDA level is in normal group 7.199 ± 1,415 ng/mL. however, after given extract show that MDA level decreases which show in the dosen 200 mg/kgBW 7,76 ± 1,64 ng/mL that nearly to the value of normal MDA level while the highest in the treatment group is 30,83 ± 0,961 ng/ml. In summary, Nanoherbal Extract of Ocimum Basilicum L has antidiabetic activity by increasing the level of insulin and antioxidant SOD level while reducing the MDA level